2020
DOI: 10.24201/fi.v60i2.2733
|View full text |Cite
|
Sign up to set email alerts
|

Los empresarios mexicanos durante el gobierno de Peña Nieto

Abstract: Con base en el examen de hechos cruciales tanto del ámbito económico como electoral, se examinan las relaciones entre el sector empresarial y el Estado mexicano durante el gobierno del presidente Enrique Peña Nieto. Tras un análisis histórico que llega a la actualidad, se estudia la relación de los empresarios con los gobiernos del pan, lo cual a su vez se relaciona directamente con la transición a la democracia en México en el año 2000. El centro del análisis es la relación de los empresarios con el gobierno … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…Along similar lines, AMLO (López Obrador, 2018: 30–33) claimed that the system of bidding for government projects was frequently rigged and as a corrective favored the publication of the terms of contracts that were signed. One international observer reported that more than three of every four public contracts under AMLO were awarded “in a ‘no-bid process’” (O’Neil, 2020), and these included three major megaprojects: construction of the Dos Bocas refinery, the Santa Lucia airport, and the Mayan Train (Alba Vega, 2020: 615). The lessons, especially in the Venezuelan case (where corruption became a major problem), are clear: The left in power needs to rely on existing institutional checks (at least for the time being) and/or develop viable new ones in order to combat the corrupt dealings that should be anticipated as a result of the policy of favoring some business groups at the expense of others.…”
Section: Relations With Business Groups In Both Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Along similar lines, AMLO (López Obrador, 2018: 30–33) claimed that the system of bidding for government projects was frequently rigged and as a corrective favored the publication of the terms of contracts that were signed. One international observer reported that more than three of every four public contracts under AMLO were awarded “in a ‘no-bid process’” (O’Neil, 2020), and these included three major megaprojects: construction of the Dos Bocas refinery, the Santa Lucia airport, and the Mayan Train (Alba Vega, 2020: 615). The lessons, especially in the Venezuelan case (where corruption became a major problem), are clear: The left in power needs to rely on existing institutional checks (at least for the time being) and/or develop viable new ones in order to combat the corrupt dealings that should be anticipated as a result of the policy of favoring some business groups at the expense of others.…”
Section: Relations With Business Groups In Both Countriesmentioning
confidence: 99%
“…Belonging to the friendly business sector, Romo served as an intermediary between AMLO and the private sector by arranging well-publicized meetings with representatives of business groups including those of Salinas, Azcárraga, Slim, and Carlos Hank González (top executive of one of Mexico’s largest banks, Banorte), all of whom indicated their openness to his candidacy. At the same time, the Consejo Coordinador Empresarial (Business Coordinating Council) maintained an officially neutral position in contrast to that of the past (Alba Vega, 2020: 613). Once AMLO was elected president, Romo occupied the position of Chief of the Office of the Presidency and created the Consejo Asesor Empresarial (Business Advisory Council), made up of Salinas, Hank González, and a representative of Televisa, among other leading businesspeople.…”
Section: Business Sector Alliances: the Venezuelan And Mexican Experi...mentioning
confidence: 99%
“…Although the level of business-friendliness varied across governments, the business sector has always been "intensely involved" in policymaking (Ondetti, 2017). Around the 1990s, the political sphere began opening to other actors and elites formed ties with other parties, particularly the PAN (Alba Vega, 2006). In addition, elites have created additional paths of influence through congressional lobbying (Alba Vega, 2006).…”
Section: Historic Tiesmentioning
confidence: 99%
“…Around the 1990s, the political sphere began opening to other actors and elites formed ties with other parties, particularly the PAN (Alba Vega, 2006). In addition, elites have created additional paths of influence through congressional lobbying (Alba Vega, 2006).…”
Section: Historic Tiesmentioning
confidence: 99%
“…Sin embargo, ni la globalización ni el neoliberalismo son procesos externos a México. Más que de una imposición por parte de actores e instituciones extranjeros, la adopción del modelo neoliberal en México resulta de decisiones por parte de líderes políticos mexicanos y de la influencia de grandes empresarios mexicanos (Alba Vega, 2006), quienes se cuentan entre los grandes beneficiarios de la apertura comercial, las privatizaciones y la desregulación de la economía mexicana. La lucha contra el neoliberalismo no se puede considerar entonces únicamente en términos antiimperialistas.…”
Section: Los Sindicatosunclassified